Cover, Content, and Editorial Note from Pengabdianmu J Pengabdian Masyarakat Vol. 5 No. 1 December 2019 - Chief Editor of PengabdianMu J Pengabdian Masyarakat (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Assalamu’alaikum Wr. Wb. Dear reader, now PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat re-published on Volume 5 Issue 1 December 2019. The success of this publication is the result of good cooperation of all parties who maintain the publishing sustainability four times a year. The publication of PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat certainly participates in disseminating the results of community services in science and technology development conducted by lecturers and researchers especially from UM Palangkaraya and other universities. This edition contains 15 articles consisting of Education, Social and Political, Islamic Studies, Engineering, and Health Science topics. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the success of the publication in the next edition in March 2020. Wassalamu’alaikum Wr. Wb. Palangka Raya, December 2019 Editor-in-Chief, signed Dr. Nurul Hikmah Kartini, S.Si., M.Pd.